TB Mukt Bharat: Challenges, Opportunities, and the Road Ahead - Sharma, Rashmi (Journal of Public and Clinical Health Research, 2026)
Tuberculosis (TB) remains one of the world’s deadliest infectious diseases, with 10.7 million cases and 1.23 million deaths globally in 2024. India is making significant strides toward tuberculosis elimination, achieving a 28% to 21% reduction in mortality and incidence, respectively and a reduction in missing cases from 15 lakhs to less than 1 (from 2015 to 2024), the most notable declines among high-burden countries. Although the original goal of TB Mukt Bharat was to eliminate tuberculosis by 2025, efforts continue vigorously under the National TB Elimination Programme (NTEP), aligned with the WHO’s End TB Strategy aiming for an 80% reduction in incidence and 90% reduction in mortality by 2030. Despite remarkable progress, challenges persist, including social determinants, drug resistance, and health system gaps. Sustaining momentum requires in-depth analysis using strategic tools such as Strengths-Weaknesses-Opportunities-Threats (SWOT) Analysis, Stakeholder Matrix, Threats-Opportunities-Weaknesses-Strengths (TOWS) Analysis, BCG Matrix, Log frame to define goal and Evaluation Framework to comprehensively track program performance to re-look again using Problem Tree & Objective Tree.